Inequality of opportunity among Indonesian school children: Education, electricity and clean water. Issue 1 (20th March 2020) - Indra, Indra; Nazara, Suahasil; Hartono, Djoni; Sumarto, Sudarno
Abstract : Purpose: The purpose of this paper is to analyze the inequality of opportunity among Indonesian school-age children from 2002 to 2012. It focuses on the possibilities of accessing basic needs, such as primary education, secondary education, electricity and clean water. Design/methodology/approach: This paper used three interrelated indicators, namely, coverage access rate, dissimilarity index and human opportunity index. It also applied Shapley decomposition to measure the contributions of each determinant of inequality opportunities. These data were obtained from the National Household Survey conducted in 2002-2012. Findings: This study revealed that the level of access to all basic needs, except clean water, was likely to increase with even distribution during the observation period. Moreover, the decomposition results showed that the education of household heads, household income and region (rural-urban) were the main contributors to the total inequality of opportunity. Originality/value: This study on the inequality of opportunity is interesting, for it is tightly related to inequality of outcome, i.e. income, expenditure and wealth. It is arguable that the inequality of outcome, nowadays, is a reflection of the past inequality in basic opportunities. Thus, the exploration of potential inequality drivers begins to be increasingly important, as it can assist the policymakers in drawing effective policies to repress the increasing trend of future inequality.